Manajemen dan Rekayasa Lalu Lintas di Ruas Jalan Brigjend Katamso, Kota Semarang, Jawa Tengah - Sholahudin, Farhan; Ma'Arif, Syamsul; Ramadhan, Muhammad (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2025)
The growth in the number of motorized vehicles, which is disproportionate to road capacity, often leads to traffic issues such as congestion, accidents, and a decline in road performance levels. This study aims to analyze traffic management and engineering on Brigjend Katamso Street to identify existing issues and provide effective and sustainable solution recommendations. The methods employed include traffic volume surveys, road inventory, vehicle speed measurement, and level of service (LoS) analysis. The analysis was conducted using calculation methods based on the 2023 Indonesian Highway Capacity Manual (PKJI). Additionally, traffic management and engineering efforts were forecasted for two years to maintain or even improve the road's performance level. The results indicate that Brigjend Katamso Street experiences high traffic density during peak hours, with the level of service at grade C, reflecting nearly unstable operational conditions. Recommendations include increasing road capacity, prioritization management, and demand management to sustain or enhance the road's performance. This study contributes to supporting the City of Semarang's policies aimed at improving traffic efficiency and safety in urban areas.